Optimising patient-initiated follow-up care – A qualitative analysis of women with breast cancer in the UK. (October 2022) - Moore, Lyndel; Matheson, Lauren; Brett, Jo; Lavender, Verna; Kendall, Anne; Lavery, Bernadette; Watson, Eila
Abstract: Purpose: Current policy in the United Kingdom (UK) recommends that people with breast cancer (PWBC) are managed in follow-up pathways that suit their needs. With an increasing trend towards patient-initiated follow-up (PIFU) pathways for PWBC, this study conducted qualitative research exploring PWBC's experiences of a nurse-led PIFU service (termed 'Supported Early Discharge') to inform how PIFU pathways could be optimised. Method: PWBC on a PIFU pathway were recruited from two UK hospitals (one large cancer centre, one district general hospital) as part of a wider mixed-methods study (N = 118). Following completion of a series of surveys, a purposive subsample of 20 women were interviewed in-depth about their experiences. Thematic analysis was conducted. Results: The majority of participants described positive views towards being on PIFU; however a significant minority struggled with uncertainties and difficulties related to: accessing ongoing care and support; performing breast self-examination (BSE); managing ongoing treatment side-effects; and fear of recurrence. Themes included: self-efficacy to manage own health; barriers and facilitators to help-seeking on a PIFU pathway; effective information sharing about side effects; preferences for personalised care; emotional wellbeing on PIFU- influences on fear of recurrence. A novel conceptual model is presented that highlights influences on self-management during PIFU. Conclusions: Findings highlight ways in which PIFU pathways could be further optimised through greater and more effective education on BSE and recognising signs of recurrence, information on when and how to seek further help with any problems, targeted provision of psychological support, and clearer signposting to support for ongoing side-effects. Highlights: Patient-initiated follow up (PIFU) pathways for people with Breast cancer could be optimised further. Greater and more effective education on recognising signs of recurrence is required. Patients need more information on when and how to seek further help during PIFU. Targeted provision of psychological support is required for some patients on PIFU.